The effect of evapo-transpiration on the stability of mature trees - Theng, Angelina Yi Tian (2016)
A tree’s stability largely depends on its root architecture as well as the soil properties it is grounded with. Numerical analysis was carried out using the SIGMA/W software, within the GEOSTUDIO suite of programs. The model was based on an experimental site located at Telok Blangah Rise where the tree of interest was a typical Samanea saman (Rain Tree). The objective of the project was to study the stability of trees, given different soil conditions caused by changing flux boundary parameters. Soil properties were previously determined and applied into the model. In addition, the centrifuge method was used to obtain the soil-water characteristic curve. Given the advance use of this technology, the experiment that would traditionally take over a couple of months to complete took instead a day to acquire the results. During the study, it was found that the lateral roots of the tree played a crucial role in resisting strong lateral wind forces. Moreover, the difference in soil conditions i.e. fully saturated or dry soil did not cause a significant difference to the force required to cause the tree to fail. Moving forward, the tree root’s architecture modeling can be further improved instead of having to use a simplified root plate system.